Prognostic value of the ascites characteristics in pseudomyxoma peritonei originating from the appendix - Wang, Bing; Sun, Xibo; Ma, Ruiqing; Yang, Zhenpeng; Tang, Huazhen; Lu, Shuai; Qu, Jinxiu; Wang, Yuying; Rao, Benqiang; Xu, Hongbin (Frontiers in Surgery, 2023)
Background Pseudomyxoma peritonei (PMP) is a rare disease, with the overall survival (OS) influenced by many factors. To date, no ascites characteristics have been reported to predict OS of patients with PMP. The present study therefore aims to describe the ascites characteristics for PMP and identify prognostic factors for survival. Methods Between June 2010 and June 2020, 473 PMP patients who underwent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy were included in a retrospective study. Survival analysis was performed with the Kaplan–Meier method by the log-rank test and a Cox proportional hazards model. Associations between categorical variables were analyzed using the chi-squared test. Results Among all included patients, 61% were women. The median OS was 47 months (range, 4–124 months) at the last follow-up in December 2020. Ascites characteristics can be divided into light blood ascites, “Jelly” mucus ascites, and faint yellow and clear ascites. Multivariate Cox analysis showed that the degree of radical surgery, ascites characteristics, and pathological grade were independently associated with OS in PMP patients. The chi-squared test documented that faint yellow “Jelly” ascites were related to low-grade PMP and light blood ascites were associated with high-grade PMP (P < 0.01). Conclusions Light blood ascites, incomplete cytoreduction surgery, and high-grade histopathology may predict poor OS in appendix-derived PMP.